Free Spirits: Spiritualism, Republicanism, and Radicalism in the Civil War Era - Hanowski, Elliot (Labour / Le Travail, 2017)
The article reviews the book, "Free Spirits: Spiritualism, Republicanism, and Radicalism in the Civil War Era," by Mark A. Lause.